Pengaruh Strategi Pembelajaran Socio Scientific Issues terhadap Keterampilan Berpikir Kritis, Keterampilan Bertanya, dan Hasil Belajar Kognitif Siswa - Fahrizal, Reza; Badrun, Listhiana Anggraini (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The purpose of this study was to determine: 1) critical thinking skills; 2) questioning skills; and 3) the effect of socio scientific issues learning strategies on students' cognitive learning outcomes. This type of research is a quasi-experimental. The research population was all students of class VIII SMP Bina Budi Mulia 2018/2019 academic year, with a total of 106 students divided into 4 classes. The sampling technique used purposive sampling technique, which was determined based on the students' abilities, so that there were 2 sample classes, namely class A as the control class with a total of 26 students, and class C as an experimental class with a total of 26 students. Based on the results of the data analysis of critical thinking skills, the pre-test results with an average of 35.18 in the control class, and 55.22 in the post-test, while the experimental class with an average pre-test value of 14.23, and post-test. test 68.76. Students' questioning skills increased from the previous control class at the first meeting by 63.66% and the second meeting by 73.33%, while the experimental class at the first meeting was 60% and the second meeting was 76.66%. The results of the analysis of students' cognitive learning outcomes obtained scores in the control class for the pre-test of 7.40% and the post-test of 66.66%, while the experimental class for the pre-test was 7.69% and the post-test was 73.07. %, with tcount = 20.292 and ttable = 0.05, so tcount > ttable. So, Ha is accepted and H0 is rejected. Thus, it can be concluded that, by using a learning strategy of socio scientific issues, it affects the cognitive learning outcomes of class VIII students of SMP Bina Budi Mulia in the 2018/2019 school year.